Histopathological Effects of Mangosteen (Garcinia mangostana L.) Peel Decoction on Betta Fish (Betta sp.) Liver - Ariesti, Wiwin; Aeniah, Siti; Halim, Shuha Ma’muriyah; Sofyantoro, Fajar; Wijayanti, Nastiti; Retnoaji, Bambang; Nuriliani, Ardaning; Saragih, Hendry T.S.S.G.; Rohmah, Zuliyati; Widiyanto, Slamet; Pusparini, Nur Ainun Oktavia; Empra, Desi Eka Putri; Septriani, Nur Indah (Universitas Islam Negeri Mataram, 2024)
Mangosteen (Garcinia mangostana L.) peel contains bioactive compounds known for their health benefits, yet potential toxicity at certain doses remains a concern. This study evaluates the histopathological effects of mangosteen peel decoction on the liver of Betta fish (Betta sp.), a sensitive model organism. Mangosteen peel decoction was prepared and administered to Betta fish at concentrations of 5, 25, and 50 ppm, with a control group receiving no treatment. Fish were observed for changes in swimming activity and appetite over five days. Liver tissues were collected, processed, and analyzed histologically to assess tissue damage including vacuolization, pyknosis, hemorrhage, and necrosis. Data were analyzed using the Kruskal-Wallis and Mann-Whitney tests. Behavioral analysis indicated a dose-dependent reduction in swimming activity and appetite in treated groups. Histopathological examination revealed significant liver damage across all treatment groups, with higher concentrations of decoction correlating with increased hemorrhage, pyknosis, and necrosis. Vacuolization was highest in the control group and lowest in the 50-ppm group. The overall hepatic damage was categorized as moderate, with the control group showing the least damage. Mangosteen peel decoction induced significant hepatic damage in Betta fish, highlighting the cytotoxic effects at higher doses. The observed behavioral and histopathological changes underscore the need for careful consideration of decoction concentrations to avoid adverse effects in aquatic organisms. This study provides crucial insights into the toxicological impacts of mangosteen peel decoction on fish liver health, emphasizing the importance of dose regulation in practical applications. Further research is recommended to explore protective measures and alternative treatments to mitigate liver damage.